Georgia, Armenia & Azerbaijan - Noble, John (My University)
A comprehensive guide to visiting Georgia, Armenia and Azerbaijan that provides information on accommodations, restaurants, sights, activities, festivals, shopping, transportation, and more, and includes suggested walking tours and itineraries, notes on the history and culture of each country, maps, and a language guide
By John Noble, Michael Kohn, Danielle Systermans. - Footscray, Vic., Lonely Planet. - [2012]. - 327 pages : illustrations (chiefly color), maps (some color) ; 20 cm.
Տվյալները՝ ինտերնետային կայքից
https://www.pdfdrive.com/lonely-planet-georgia-armenia-azerbaijan-d162366184.htm
Keywords: Georgia-Sociography; Armenia-Sociography; Azerbaijan-Sociography